Study on the damage and failure behavior of coal exposed to acid corrosion under impact load - Zhaoying Chen; Wenmei Han; Xiang Zheng; Hongtai Liu (PLoS ONE, 2025)
The depth of coal mining is continuously increasing. In the process of deep underground coal mining, the hydrological conditions of coal seams are complex, with some coal seams subjected to corrosion by acidic water. Acidic water-rock chemical interactions significantly degrade the mechanical properties of coal rocks. Concurrently, dynamic loads from frequent blasting and mining-induced rockbursts pose severe threats to mining safety. Investigating the dynamic properties of coal exposed to acidic water environments is crucial for ensuring safe coal mining operations. This study investigated anthracite coal as the research subject. Dynamic Brazilian splitting tests were conducted using a Split Hopkinson Pressure Bar (SHPB) apparatus to evaluate the mechanical behaviour of coal samples. A three-dimensional SHPB numerical model was constructed using the continuous-discrete coupling method and Flat Joint Model(FJM). The damage mechanism of coal under the action of acidic solutions was analyzed from the perspectives of dynamic mechanical response, damage evolution, and failure modes. The results indicate that the dynamic tensile strength of coal samples after exposure to acidic solutions is lower than that of raw coal samples, with strength decreasing in order: raw coal > pH 4 > pH 2. Moreover, with increasing impact velocity or loading rate, the dynamic tensile strength, degree of fragmentation, and dissipated energy of three types of samples increase linearly. In the dynamic stress–time response curve, during the initial stress rise phase, the model undergoes approximately linear elastic deformation with only a small number of microcracks forming. During unloading, the number of cracks continues to increase but at a reduced rate. Under the same impact velocities, the total number of cracks formed upon failure follows the order: pH2 > pH4 > raw coal.